PEMBUATAN SALURAN KELILING UNTUK MENGATASI BANJIR (Studi Kasus Perumahan PNS Kota Tarakan, Kalimantan Utara) - Kiki Frida Sulistyani (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2016)
So far we know making a ring road outside the city or county to mengartasi traffic density on roads in urban areas. To address the housing PNS flooding caused by the availability of water from surrounding areas due to the location of residential housing in the river valley, then in fashion channel surround housing. Given the rapid development in the town of Tarakan, the manufacturing channel surround using the C = 0,5 assuming land use layout around PNS housing has become a residential areal. This meant that the planned channel can still be used to the area around the housing PNS into a residential area. Calculation results show precipitation method Log Pearson type III at Q = 162 459 mm 10 th and 25 th Q = 183 888 mm. The area around the housing PNS affecting the flood housing PNS is divided into 7 sub-watershed. Channel calculation using trapezoid channel 2 alterbatif namely the pair of stone and concrete vertical channel. Dimensional calculation results obtained from the largest channel for vertical channel B = 5.0 m and H = 2.5 m.